The Brazilian and United States experiences on the empowerment of people with disabilities through technologies - DaLee, Christine Koury; DaLee, Jason (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2018)
Technologies have long enabled individuals to overcome natural restriction and human limitations. This paper highlights some of Brazil’s and United States’ policies on the subject. Additionally, brings examples of assistive technology and ambient assisted living available in U.S.A market to support people with intellectual disabilities. Keywords: Assistive technology. Ambient assisted living. Smart homes. Universal designing. Cognitive disabilities. As tecnologias sempre permitiram aos indivíduos superar restrições naturais e limitações humanas. Este artigo destaca algumas das políticas do Brasil e dos Estados Unidos nesse campo. Além disso, traz exemplos de tecnologia assistiva e ambient assisted living disponíveis no mercado americano para apoiar pessoas com deficiência intelectual. Palavras-chave: Tecnologia assistiva. Ambiente assistido. Casas inteligentes. Design universal. Dificuldades cognitivas. Link:http://revista.ibict.br/inclusao/article/view/4036/3373